Analysis Of The Quranic Translation In Dayak Kanayatn Language: History, Characteristics, And Its Significance For The West Kalimantan Community - Parwanto, Wendi; Yuliarto, Udi; Putra, Hepni; Husnaini, Ica Fauziah; Akbar, Taufik; Fahm, AbdulGafar Olawale (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2024)
The aim of this study is to describe three major features of the Quranic Translation in Dayak Kanayatn language. Type of this study is a library research because it examines and analyzes printed literature, specifically the translation of the Qur'an. The method used is descriptive-analytical. The conclusion of this study explains that: First, the history of writing the Quranic Translation in Dayak Kanayatn language began in 2012 with three Quranic scholars from IAIN Pontianak and several other members as local language proofreaders. This translation is complete with 30 Juz, 1173 pages, and has been printed in 2,000 copies and sent to several ASEAN and European countries. Second, the translation systematics use a regular translation model, but with added footnotes, especially to explain terms or verses that require additional clarification. Third, the significance of this translation is quite good, especially for the community or individuals who understand the Dayak Kanayatn language.